University spin-off firms in sustainable energy in five countries: What determines their reaching of the market? - Marina Van Geenhuizen; Razie Nejabat (European Regional Science Association (ERSA), 2016)
An entrepreneurial perspective to introduction of sustainable energy solutions to the market has been recognized as important for decades, but mainly concerning large firms. Today, attention is increasingly turning to young high-technology ventures which, compared to large incumbents, are more flexible, creative, responsive and willing to take risks enabling them to work as a trigger or accelerator of profound changes. At the same time, these young firms suffer from a lack of resources, specifically investment capital, the last mainly caused by a slow development due to resistance from society, among others, existing energy infrastructures ('valley of death'). In this context, an often advised strategy is to partner with a larger company. This paper explores the time dimension in market introduction of sustainable energy solutions while taking an in-depth approach to collaboration and investment capital amidst a set of other firm-specific and external factors. First, we compare the five countries, Netherlands, Norway, Sweden, Denmark and Finland, with regard to favorable circumstances to adoption of sustainable energy solutions, particularly continuity in supporting policies. Next, we build a carefully selected sample of 37 university spin-off firms representing different 'theoretical positions' regarding country, but also established collaboration networks, amount of investment capital granted, and type of energy system - solar, wind, biomass, etc. - and we apply rough-set analysis as a 'qualitative' causal analysis. In addition, we deploy five in-depth case studies for deepening understanding. We found that out of nine firm-specific and firm-external factors, three factors have a strong influence on speed of market introduction. These are first of all country, but also type of energy technology (system) and richness in collaboration networks. Country was found to have a positive influence on reaching the market at a higher level of innovation (Nordic 'innovation leader' countries) and, conversely, a negative influence at lower levels of innovation (Netherlands and Norway). Furthermore, rich network collaboration turned out to work positively in an already positive situation ('innovation leader' country). Lacking such collaboration contributed to problematic developments, specifically in combination with solar technology. Evidence on influence of lack of capital investment turned out to be rather weak. Further, the case study analysis yielded the additional insight that speed in market introduction may also work negatively, namely, if large amounts of investment capital put pressure on the firm and market introduction occurs actually too early. The paper concludes with issues on 'theoretical' generalization, extending the sample to a larger random sample, and additional research questions.
Keywords: D22; Q42; Q48; M13; 330; Sustainable energy (system); young ventures; market introduction; national innovation system; collaboration; investment capital